Causes and optimization of the false alarm rate of code review system - Yuanying XIAO; Yaodong YOU; Lixi XIANG (Dianxin kexue)
Code review technology has become a pivotal part in the construction of network security.Analysis of the test reports obtained by the current code auditing system shows that there are many false positives in the report.The shortcomings in the development of the code audit system were summarized,the principles of different detection algorithms were briefly described,the causes of false alarm rates were analyzed,corresponding optimization ideas were proposed,the technical principles of optimization were explained,and the application scenarios of optimization schemes were described.